2023
DOI: 10.1029/2023jd039196
|View full text |Cite
|
Sign up to set email alerts
|

Mesospheric Water Vapor in 2022

Gerald E. Nedoluha,
R. Michael Gomez,
Ian Boyd
et al.

Abstract: The eruption of the Hunga Tonga undersea volcano in January 2022 injected water vapor to altitudes as high as 53 km, but also an unprecedented and much larger amount of water vapor into the stratosphere. Several months after the eruption, measurements from the Aura Microwave Limb Sounder (MLS) and from three ground‐based Water Vapor Millimeter Wave Spectrometer instruments began to measure record‐high amounts of water vapor in the mesosphere over a wide range of latitudes. While there are indications that some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The Tonga underwater volcano's exceptional eruption injected an unprecedented amount of water vapor directly into the stratosphere (Carr et al, 2022;Millán et al, 2022;Xu et al, 2022) and substantially increased the water vapor concentration in the mesosphere in 2022 (Nedoluha et al, 2023). While the initial injection plume at 20°S reached the upper stratosphere (Carr et al, 2022, Millán et al,2022 showed that after three months, this excess water vapor settled near the 20 hPa altitude in a latitude band from 30°S to 5°N.…”
Section: Introductionmentioning
confidence: 99%
“…The Tonga underwater volcano's exceptional eruption injected an unprecedented amount of water vapor directly into the stratosphere (Carr et al, 2022;Millán et al, 2022;Xu et al, 2022) and substantially increased the water vapor concentration in the mesosphere in 2022 (Nedoluha et al, 2023). While the initial injection plume at 20°S reached the upper stratosphere (Carr et al, 2022, Millán et al,2022 showed that after three months, this excess water vapor settled near the 20 hPa altitude in a latitude band from 30°S to 5°N.…”
Section: Introductionmentioning
confidence: 99%
“…Fleming et al (2024) have presented some calculations of the effect of this additional H 2 O on O 3 and temperature over the next decade. Nedoluha et al (2023b) (hereafter N23) documented an increase in mesospheric H 2 O in 2022. Measurements from MLS and three ground-based microwave instruments often recorded the highest H 2 O mixing ratio anomalies ever seen at particular locations.…”
Section: Introductionmentioning
confidence: 99%
“…Nedoluha et al. (2023b) (hereafter N23) documented an increase in mesospheric H 2 O in 2022. Measurements from MLS and three ground‐based microwave instruments often recorded the highest H 2 O mixing ratio anomalies ever seen at particular locations.…”
Section: Introductionmentioning
confidence: 99%